2020
DOI: 10.1111/jsap.13255
|View full text |Cite
|
Sign up to set email alerts
|

131treatment in dogs with hyperthyroidism caused by a non‐resectable ectopic thyroid tumour: 5 cases (2008‐2019)

Abstract: Objectives This study aimed to describe the clinical and diagnostic characteristics, as well as outcomes of radioiodine treatment in dogs with hyperthyroidism caused by a non‐resectable ectopic thyroid tumour. Materials and Methods This retrospective study reviewed the medical records between 2008 and 2018 of dogs diagnosed with hyperthyroidism secondary to a non‐resectable ectopic thyroid tumour and treated with radioiodine. Results Five dogs were included in the study. Three dogs had sublingual ectopic tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…All dogs with functional tumours became euthyroid following 131 I. A recent study of five dogs with ectopic functional thyroid carcinomas treated with 131 I also described normalization of T4 in all dogs 32 . This raises a question around the importance of achieving a measurable response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All dogs with functional tumours became euthyroid following 131 I. A recent study of five dogs with ectopic functional thyroid carcinomas treated with 131 I also described normalization of T4 in all dogs 32 . This raises a question around the importance of achieving a measurable response.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of five dogs with ectopic functional thyroid carcinomas treated with 131 I also described normalization of T4 in all dogs. 32 This raises a question around the importance of achieving a measurable response. Turrel et al found no difference in the MST of dogs treated with 131 I that had subsequent tumour resection compared with 131 I alone, postulating no benefit in reducing tumour burden.…”
Section: Discussionmentioning
confidence: 99%
“…De igual forma la radioterapia con yodo en un estudio denominado "Treatment with hyperthyroidism caused by a non-resectable ectopic thyroid tumour: 5 cases (2008-2019)" y realizado por (Lyssens et al, 2021), demostró una diminución del tamaño de las masas ectópicas en tanto que las concentraciones totales de tiroxina volvieron a los rangos de referencia en todos los perros.…”
Section: Los Tumores Malignosunclassified
“…Vol.8-N° 1, 2024, pp. 3922-3940 Journal Scientific MQRInvestigar 3928 mejorar el diagnóstico, la estadificación y la planificación del tratamiento del carcinoma de tiroides humano (Lyssens et al, 2021).…”
Section: Introductionunclassified